Policy Analysis of The Regional Government of Bengkulu Province in Supporting Fiscal Independence in The Autonomy Era - Yohanes Susanto; Panji Suminar; Sugeng Suharto (Yayasan Ilomata, 2020)
This study aims to measure how the degree of fiscal independence of Bengkulu Province in the era of autonomy and to find out how the policies of the Bengkulu Province local government in supporting fiscal independence in the era of autonomy. This research uses descriptive quantitative method using secondary data. Data analysis was performed using multiple linear regression model data analysis techniques. Based on the results of the study, it is known that the degree of fiscal independence of Bengkulu Province in the period 2013-2017 is for the proportion of PAD to TPD obtained an average of 31.79% based on the interval scale is stated to be sufficient, BHPBP against TPD obtained an average result of 4, 37% based on the interval scale was stated to be very poor, while the DAU and DAK against the TPD obtained an average result of 54.30% with the interval scale declared very good. The policy of the Bengkulu Province local government in supporting fiscal independence has made policies to create a conducive climate for investors, policies to encourage regional economic growth and regional spending are strived to support the achievement of development goals effectively and efficiently